2020
DOI: 10.3390/agronomy10030352
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Nitrogen Fertilization to Improve Qualitative Performances and Physiological and Yield Responses of Potato (Solanum tuberosum L.)

Abstract: Potato is often produced by adopting high nitrogen (N) external inputs to maximize its yield, although the possible agronomic and qualitative benefits of a N over-fertilization to the crop are scarcely demonstrated. Therefore, our aim was to determine, over two years, the effect of three N fertilization rates (0, 140 and 280 kg ha −1 , referred to as N0, N140 and N280) simultaneously on the crop physiology, yield components, N use efficiency and tuber chemical composition of cv. Bellini. Throughout the field m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 62 publications
2
14
0
1
Order By: Relevance
“…It has been reported that potato tuber mineral composition is significantly affected by N fertilizer management 5 . The N fertilizer management is critical for better marketable tuber yield, as well as marketable attributes such as specific gravity, total soluble solids and starch in potatoes 31‐33 . The present study demonstrated that N sources have specific positive effects on tuber quality.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that potato tuber mineral composition is significantly affected by N fertilizer management 5 . The N fertilizer management is critical for better marketable tuber yield, as well as marketable attributes such as specific gravity, total soluble solids and starch in potatoes 31‐33 . The present study demonstrated that N sources have specific positive effects on tuber quality.…”
Section: Discussionsupporting
confidence: 53%
“…For many years, research efforts on potato production have focused on increasing yield disregarding important factors such as the use of resources and the environmental impact of these agricultural practices (Bulgari et al 2015). The main objective of modern agriculture, however, is reducing the environmental impact derived from potato-management practices while ensuring high and stable yield and high tuber quality (Lombardo et al 2020). Tuber quality is determined by marketable size, shape, absence of defects, flavour, colour, nutritional composition (vitamin C, protein and beneficial elements) and the texture of cooked or processed tubers (Stark et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable agronomic measure for enhancing early potato organic production is represented by an adequate nutrient management [27] and an improvement of fertilization use efficiency [28]. Particularly, this may be achievable by applying arbuscular mycorrhizal fungi (AMF), obligate symbionts of the vast majority of land plants [29].…”
Section: Introductionmentioning
confidence: 99%